Final answer:
To find (h∘g)(a), first calculate g(a) which is 2*a, then substitute this into h(x) to get h(2a) = (2a)² + 4, and simplify to 4a² + 4.
Step-by-step explanation:
The student is asking to find the value of “(h∘g)(a)”, which means we are looking for the composition of the functions h(x) and g(x) evaluated at 'a'. Since g(x)=2x and h(x)=x²+4, we first apply the function g to 'a', resulting in 2a, and then apply the function h to this result. Thus, we need to calculate h(g(a)), which is h(2a) = (2a)² + 4.
The next step is to substitute 2a into the equation h(x) = x² + 4: (2a)² + 4 = 4a² + 4. This gives us the value of the composition of functions h(g(a)) at the point 'a'. This procedure demonstrates an understanding of function composition which is a fundamental concept in algebra and precalculus.